Lymphadenopathy in rheumatic patients. Issue 3 (March 1987) - Kelly, C A; Malcolm, A J; Griffiths, I
Abstract : Lymph node biopsy specimens from 22 patients with chronic inflammatory joint disease have been studied. The histology has been reviewed and immunoperoxidase staining carried out for the major immunoglobulin heavy and light chains, macrophage markers, and MT1, MB1 surface markers. Although two of these patients had been initially diagnosed and treated for malignant lymphoma, the clinical course has not substantiated the diagnosis, and on review malignancy could not be identified in any of the biopsy specimens. Careful attention to specific histological features, together with adequate clinical information, is therefore essential if the true nature of the lymph node enlargement is to be recognised. Clinical review of the 22 patients suggested that lymphadenopathy may, in some cases, be an early feature of inflammatory polyarthritis, and this was supported by the observation that 20% of patients with otherwise unexplained reactive lymphadenopathy developed an inflammatory polyarthropathy within one year of biopsy.